1974
DOI: 10.1113/jphysiol.1974.sp010767
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane potentials in guinea‐pig hepatocytes

Abstract: SUMMARY1. In pieces of guinea-pig liver with an intact capsule, the mean resting potential (E) is -49-8 mV, close to the value for in vivo hepatocytes and significantly higher than a similar preparation of rat liver. E is considerably less than the calculated K equilibrium potential of about -90 mV.2. Changes in [K+]. in the range of 0-10 mm produce almost no change in E. At [K+] [Cli]. in opposite directions to maximize predicted changes in E also has only a minimal effect on E.4. Cyanide (5 mM) or ouabain (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

1977
1977
1994
1994

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…In some of these cells, biologically important electrical responses can be detected (e.g. action potentials ; Kaneko, 1969) and electrogenic effects (Heller & van der Kloot, 1974;Petersen, 1974). Most recently, Table 4…”
Section: ;mentioning
confidence: 99%
“…In some of these cells, biologically important electrical responses can be detected (e.g. action potentials ; Kaneko, 1969) and electrogenic effects (Heller & van der Kloot, 1974;Petersen, 1974). Most recently, Table 4…”
Section: ;mentioning
confidence: 99%
“…A high K+ and low Na+ concentration within the cells is maintained by a coupled ouabain-sensitive active transport (Elshove & van Rossum, 1963;Haylett & Jenkinson, 1972a, b;Heller & van der Kloot, 1974; , exhibiting an electrogenic component (Claret & Mazet, 1972 a;Graf & Petersen, 1974).…”
mentioning
confidence: 99%
“…Lassen et al, working with Ehrlich ascites tumor cells (21) or Amphiuma erythrocytes (22), found that following impalement there was a rapid decay of the membrane potential with a half time of about 1 ms. After the decay, the steady-state potential was no longer sensitive to the K § concentration of the medium. They calculate that, given the lesser surface areas of mitochondria, the decay after impalement should be much faster (21 5,6,7,11,12,17,18,37,39,40,41]). Potentials which do not decay significantly with time have been recorded (5,6,7,12,17,(37)(38)(39)(40)(41).…”
mentioning
confidence: 99%
“…They calculate that, given the lesser surface areas of mitochondria, the decay after impalement should be much faster (21 5,6,7,11,12,17,18,37,39,40,41]). Potentials which do not decay significantly with time have been recorded (5,6,7,12,17,(37)(38)(39)(40)(41). Some of these potentials were found to be sensitive to the K § concentration in the medium (5,6,12,39,40).…”
mentioning
confidence: 99%